Preparation and Properties of Antibacterial Polydopamine and Nano-Hydroxyapatite Modified Polyethylene Terephthalate Artificial Ligament - Wu, Yang; Zhang, Yuhan; Zhang, Ren; Chen, Shiyi (Frontiers in Bioengineering and Biotechnology, 2021)
Due to its great biomechanical property, Polyethylene terephthalate (PET) artificial ligament has become one of the most promising allografts for anterior cruciate ligament (ACL) reconstruction. However, because of its chemical and biological inertness, PET is not a favored scaffold material for osteoblasts growth which promotes the ligament-bone healing. Meanwhile, in consideration of prevention of potential infection, the prophylactic injection of antibiotic was used as a postoperative standard procedure, but also has the increasing risk of bacterial resistance. To face these two contradictions, in this article we coated a polydopamine (PDA) nano layer on the PET ligament and used the coating as the adhesion interlayer to introduce nano-hydroxyapatite (nHA) and silver atoms to the surface of PET ligament. Because of the mild self-polymerization reaction of dopamine, the thermogravity analysis (TGA), Raman spectrum and tensile test results show that the modification procedure have no negative effects on the chemical stability and mechanical properties of the PET. The results of NIH3T3 cell culture show that the PDA and nHA could effectively improve the biocompatibility of PET artificial ligament for fibroblast growth, and staphylococcus aureus antibacterial test results show that the Ag atom provided antibacterial effect for PET ligament. As shown in this paper, the nano PDA coating modification procedure could not only preserve the advantages of PET, but also introduce new performance characteristics to PET, which opens the door for further functionalization of PET artificial ligament for its advanced development and Application.